From melting pot to witch's cauldron : how multiculturalism failed America - Caravantes, Ernesto (Lanham, Md. : Hamilton Books/Rowman & Littlefield, 2010)
This book explores what can happen when good intentions go askew. The author points out that the original wishes of the founders of the American Republic, as well as the desires of modern luminaries like Dr. Martin Luther King, Jr. and Cesar Chavez, have not been realized. He traces this problem to the radical activism of the 1960s, which introduced the notion of multiculturalism. In so doing, that activism completely erased all chances of seeing the dreams of these activists being brought into fruition. The author points out that the true and original aim of the multiculturalism movement was to have people of divergent ethnic backgrounds become unified by their differences, yet what is occurring is just the opposite. Xenophobia and ethno-centrism have developed among the different ethnic groups in the United States.
Plymouth Rock -- The Enlightenment -- The African slaves in America -- The Scandinavian and Irish migration -- The Mexican border is re-established -- The arrival of the Jews -- The 1960s mentality started with two bullets -- The effects of the civil rights movement -- Martin Luther King, Jr. and Cesar Chavez would be ashamed -- The formation of the ghetto and the barrio -- Multiculturalism in league with identity politics -- Multiculturalism in league with political correctness -- Let us define "culture" -- Whose culture is it, anyway? -- What "failure" implies -- Why the experiment failed -- The role of parents -- The role of the universities -- The roles of the media -- Undoing the damage -- The 21st century American -- Marching forward and closing thoughts.
Keywords: Multiculturalism -- United States; Ethnicity -- United States; Cultural pluralism -- United States; United States -- Ethnic relations